Difference between revisions of "009B Sample Midterm 1, Problem 3"

From Math Wiki
Jump to navigation Jump to search
Line 8: Line 8:
 
!Foundations:    
 
!Foundations:    
 
|-
 
|-
|Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du.</math>
+
|'''1.''' Integration by parts tells us that <math style="vertical-align: -12px">\int u~dv=uv-\int v~du.</math>
 
|-
 
|-
|How would you integrate <math style="vertical-align: -12px">\int x\ln x~dx?</math>
+
|'''2.''' How would you integrate <math style="vertical-align: -12px">\int x\ln x~dx?</math>
 
|-
 
|-
 
|
 
|
Line 28: Line 28:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We proceed using integration by parts. Let <math style="vertical-align: 0px">u=x^2</math> and <math style="vertical-align: 0px">dv=e^xdx</math>. Then, <math style="vertical-align: 0px">du=2xdx</math> and <math style="vertical-align: 0px">v=e^x</math>.
+
|We proceed using integration by parts. Let <math style="vertical-align: 0px">u=x^2</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> Then, <math style="vertical-align: 0px">du=2xdx</math> and <math style="vertical-align: 0px">v=e^x.</math>
 
|-
 
|-
 
|Therefore, we have
 
|Therefore, we have
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -12px">\int x^2 e^x~dx=x^2e^x-\int 2xe^x~dx</math>.
+
|
 +
::<math style="vertical-align: -12px">\int x^2 e^x~dx=x^2e^x-\int 2xe^x~dx.</math>
 
|}
 
|}
  
Line 38: Line 39:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we need to use integration by parts again. Let <math style="vertical-align: 0px">u=2x</math> and <math style="vertical-align: 0px">dv=e^xdx</math>. Then, <math style="vertical-align: 0px">du=2dx</math> and <math style="vertical-align: 0px">v=e^x</math>.
+
|Now, we need to use integration by parts again. Let <math style="vertical-align: 0px">u=2x</math> and <math style="vertical-align: 0px">dv=e^xdx.</math> Then, <math style="vertical-align: 0px">du=2dx</math> and <math style="vertical-align: 0px">v=e^x.</math>
 
|-
 
|-
 
|Building on the previous step, we have
 
|Building on the previous step, we have
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -15px">\int x^2 e^x~dx=x^2e^x-\bigg(2xe^x-\int 2e^x~dx\bigg)=x^2e^x-2xe^x+2e^x+C</math>.
+
|
 +
::<math>\begin{array}{rcl}
 +
\displaystyle{\int x^2 e^x~dx} & = & \displaystyle{x^2e^x-\bigg(2xe^x-\int 2e^x~dx\bigg)}\\
 +
&&\\
 +
& = & \displaystyle{x^2e^x-2xe^x+2e^x+C.}\\
 +
\end{array}</math>
 
|}
 
|}
  
Line 49: Line 55:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We proceed using integration by parts. Let <math style="vertical-align: -1px">u=\ln x</math> and <math style="vertical-align: 0px">dv=x^3dx</math>. Then, <math style="vertical-align: -13px">du=\frac{1}{x}dx</math> and <math style="vertical-align: -14px">v=\frac{x^4}{4}</math>.
+
|We proceed using integration by parts. Let <math style="vertical-align: -1px">u=\ln x</math> and <math style="vertical-align: 0px">dv=x^3dx.</math> Then, <math style="vertical-align: -13px">du=\frac{1}{x}dx</math> and <math style="vertical-align: -14px">v=\frac{x^4}{4}.</math>
 
|-
 
|-
 
|Therefore, we have
 
|Therefore, we have
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -20px">\int_{1}^{e} x^3\ln x~dx=\left.\ln x \bigg(\frac{x^4}{4}\bigg)\right|_{1}^{e}-\int_1^e \frac{x^3}{4}~dx=\left.\ln x \bigg(\frac{x^4}{4}\bigg)-\frac{x^4}{16}\right|_{1}^{e}</math>.
+
|  
|-
+
::<math>\begin{array}{rcl}
|
+
\displaystyle{\int_{1}^{e} x^3\ln x~dx} & = & \displaystyle{\left.\ln x \bigg(\frac{x^4}{4}\bigg)\right|_{1}^{e}-\int_1^e \frac{x^3}{4}~dx }\\
 +
&&\\
 +
& = & \displaystyle{\left.\ln x \bigg(\frac{x^4}{4}\bigg)-\frac{x^4}{16}\right|_{1}^{e}.}\\
 +
\end{array}</math>
 
|}
 
|}
  
Line 63: Line 72:
 
|Now, we evaluate to get  
 
|Now, we evaluate to get  
 
|-
 
|-
| &nbsp;&nbsp; <math style="vertical-align: -17px">\int_{1}^{e} x^3\ln x~dx=\bigg((\ln e) \frac{e^4}{4}-\frac{e^4}{16}\bigg)-\bigg((\ln 1) \frac{1^4}{4}-\frac{1^4}{16}\bigg)=\frac{e^4}{4}-\frac{e^4}{16}+\frac{1}{16}=\frac{3e^4+1}{16}</math>.
+
|  
|-
+
::<math>\begin{array}{rcl}
|
+
\displaystyle{\int_{1}^{e} x^3\ln x~dx} & = & \displaystyle{\bigg((\ln e) \frac{e^4}{4}-\frac{e^4}{16}\bigg)-\bigg((\ln 1) \frac{1^4}{4}-\frac{1^4}{16}\bigg)}\\
|-
+
&&\\
|
+
& = & \displaystyle{\frac{e^4}{4}-\frac{e^4}{16}+\frac{1}{16}}\\
 +
&&\\
 +
& = & \displaystyle{\frac{3e^4+1}{16}.}\\
 +
\end{array}</math>
 
|}
 
|}
  

Revision as of 13:07, 18 April 2016

Evaluate the indefinite and definite integrals.

a)
b)


Foundations:  
1. Integration by parts tells us that
2. How would you integrate
You could use integration by parts.
Let and Then, and
Thus,

Solution:

(a)

Step 1:  
We proceed using integration by parts. Let and Then, and
Therefore, we have
Step 2:  
Now, we need to use integration by parts again. Let and Then, and
Building on the previous step, we have

(b)

Step 1:  
We proceed using integration by parts. Let and Then, and
Therefore, we have
Step 2:  
Now, we evaluate to get
Final Answer:  
(a)  
(b)  

Return to Sample Exam